1966
DOI: 10.1128/aem.14.4.654-664.1966
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inhibition and Repression on the Utilization of Substrates by Heterogeneous Bacterial Communities

Abstract: STUMM-ZOLLINGER, ELISABETH (Harvard University, Cambridge, Mass.). Effects of inhibition and repression on the utilization of substrates by heterogeneous bacterial communities. Appl. Microbiol. 14:654-664. 1966.-This investigation attempts to evaluate to what extent enzyme inhibition and repression by metabolites, indigenous to the cell, are significant phenomena in natural microbial communities. Three case histories of the kinetics of substrate utilization and growth in multisubstrate media by heterogeneous b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1976
1976
1989
1989

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…strain ANL was able to utilize simultaneously low concentrations of aniline and glucose. The ability of heterogeneous bacterial communities to metabolize mixtures of carbon compounds simultaneously has long been known (15), and the simultaneous use of several substrates by pure cultures of bacteria has been reviewed by Harder and Dijkhuizen (4). Recently, it was shown that a synthetic compound (methylene chloride) can be degraded simultaneously with acetate by a pure culture of bacteria (7).…”
Section: Discussionmentioning
confidence: 99%
“…strain ANL was able to utilize simultaneously low concentrations of aniline and glucose. The ability of heterogeneous bacterial communities to metabolize mixtures of carbon compounds simultaneously has long been known (15), and the simultaneous use of several substrates by pure cultures of bacteria has been reviewed by Harder and Dijkhuizen (4). Recently, it was shown that a synthetic compound (methylene chloride) can be degraded simultaneously with acetate by a pure culture of bacteria (7).…”
Section: Discussionmentioning
confidence: 99%
“…The four polysaccharides studied in this investigation were each broken down at different rates and to different degrees by faecal bacteria. The rapid breakdown of starch suggested that, when a mixture of NSP and starch was available to gut bacteria, fermentation of NSP might be affected by the operation of catabolite control mechanisms [25,26]. The results shown in Fig.…”
Section: Significance Of Polysaccharide Fermentation In the Large Gutmentioning
confidence: 94%
“…Experimental evidence for sequential, concurrent, or interactive substrate utilization patterns have been reported, but the results have usually been explained qualitatively in terms of enzyme induction, the presence of constitutive enzymes, or competitive inhibition. Diauxic growth, with preference for glucose, has been reported by numerous investigators .1- 6 The lag phase between glucose depletion and utilization of the other target substrates varies from 1-4 h7 to 16 h. 8 The lag phase is ascribed to physiological adaptation rather than mu-Biotechnology and Bioengineering, Vol. XXIV, Pp.…”
Section: Introductionmentioning
confidence: 96%